Pendampingan Pengelolaan Bank Sampah di Kelurahan Karang Asam Ulu Kota Samarinda : Optimalisasi Manajemen Keuangan dan Pengolahan Sampah - Puspitasari, Novianti; Suryadi, Ahmad; Sandyanegara, Aryasena Bela; Nursari, Ayla; Pusparini, Faradilla; Rezky, Muhammad; Kalista, Nazwa Nur Maulida Qintani; Rahayu, Rizqi Widya; Gunawan, Santika; Wijaya, Zhienka Putri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to optimize the management of financial transactions at waste banks by increasing the knowledge of waste bank officers. Apart from that, this activity also seeks to help the community in handling and processing waste into products that are valuable and beneficial for the environment. The method for implementing this activity uses persuasive mentoring and socialization with stages of preparation, socialization, implementation, and evaluation. This activity was attended by 30 participants consisting of family representatives and women who manage the waste bank in Karang Asam Ulu Village. The evaluation instrument for this service activity is in the form of distributing questionnaires and analyzing them descriptively. The results of this service show that the knowledge of the women managing the Ramli